P27. The fasting hormone FGF21-an alternative therapy for Alzheimer's disease?. Issue 8 (August 2018) - Kuhla, A.; Rühlmann, C.; Dannehl, D.; Adams, A.C.; Lindner, T.; Stenzel, J.; Kurth, J.; Krause, B.J.; Vollmar, B.
Abstract : Background: Lipolysis is regulated by PPAR α / γ and its target genes apoE and ABCA1, which not only control the transport of cholesterol but also the proteolytic degradation of A β -peptide (A β ) plaques, which are found to be deposited in increased number in Alzheimer's disease (AD). Accordingly, it was shown that PPAR γ -activation stimulates A β -degradation, in an ABCA1- and apoE-dependent manner. Thus, it is reasonable to assume that increased lipolysis may be neuroprotective and could in part minimize the risk of developing dementia. Lipolysis is intensified during fasting, causing a rise in FGF21 levels, which also acts as a key mediator for PPAR α / γ . Therefore, we hypothesized that the FGF21-PPAR pathway may contribute to A β -clearance, via apoE and ABCA1. This in turn may enhance glucose metabolism, leading to improvements in cognition. Methods and results: In line with this hypothesis, we were able to show in vitro that application of wild type FGF21 or an FGF21 Analogue (LY2405319; LY; Eli Lilly) to neurons as well as in glial cells, significantly increases mRNA expression of apoE and ABCA1. Application of LY to ex vivo brain slices of APPswe/PS1 Δ e9 (APP/PS1) mice, an AD-mouse model, reduces A β -plaques of up to 30% in comparison to control. These mice are also characterized by diminished glucose uptake in cognitive brain areas, as demonstrated by 18-FDG-positron emission tomography (FDG-PET). Interestingly, daily LY-application for 16 weeks augments central glucose metabolism in APP/PS1 mice, as indicated by an increased FDG uptake up to the value of control mice (C57BL6 mice). Conclusion: Thus, we propose that FGF21 activates apoE/ABCA1-induced degradation of A β -plaques, leading to enhanced cognitive function, functionally evidenced by an increased glucose metabolism. Further experiments are necessary to evaluate FGF21 as a therapeutic option for treatment of AD. Funded by theGerman Research Foundation (KU 3280/1-1 ).